Design of Desktop-Based Student Learning Style and Personality Quiz Application with Microsoft Visual Basic Net 8.0 - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Fali, Rifki; Tanzila, Laili; Sarumaha, Matius Irvan; Zai, Frans Pratamarifai Doya (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
In education, learning style and personality play an important role because they influence how individuals perceive and absorb information. Educators can build more inclusive and successful learning environments by implementing strategies to accommodate a variety of learning styles and personalities. The learning style and personality quiz application was created with Microsoft Visual Basic 8.0. The purpose of this application is to find out the learning style and personality of students. By knowing their learning style and personality, students can understand themselves and make it easier to choose the learning method to use. The method used in designing this application is the waterfall method. The method begins with the analysis, design, coding, testing and maintenance stages. The learning style and personality quiz application has been tested on several students of the Information Technology and Computer Education Study Program, Medan State University for three weeks, the results show that the learning style and personality quiz application can help in selecting effective learning methods and understanding one's own character.